IDENTIFIKASI SIKAP DAN INTERAKSI SOSIAL SISWA PADA PEMBELAJARAN MATEMATIKA DENGAN MODEL COLLABORATIVE LEARNING PADA POKOK BAHASAN KUBUS DAN BALOK KELAS VIII DI SMP NEGERI 4 JEMBER - Putra, Rizki Cahya Eka; Trapsilasiwi, Dinawati; Kurniati, Dian (Kadikma, 2017)
Abstract. The purpose of this research is describing the attitude preference and the social interaction of students in learning mathematics by using Collaborating Learning model. The data collection method was observation in a class of SMPN 4 Jember, which’s 8A. The analysis can be seen from the students’ observation sheet including the attitude indicator to mathematics learning and the indicator of social interaction in the mathematics learning. After that, the researcher examined the relation between the result of the observation and the factors which’s influencing the students’ attitude and social interaction. The students’ attitude to the mathematics learning has three components which are (1) Students’ emotion, (2) Students’ point of view to the mathematics learning, and (3) students’ confidence. The social interaction can be happened under condition (1) there is a contact (2) there is a communication. The students have a preference to have a good attitude to the mathematics learning which’s shown by some positive scores in the component of attitude. The students’ social interaction is disposed to be positive attitude which’s shown by a good cooperation among students in a group so that, they got a maximal result of their study. Keywords: Attitude, Social Interaction, and Collaborative Learning